2018
DOI: 10.29245/2578-3009/2018/si.1115
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Tetanus Elimination (MNTE) in The WHO African Region

Abstract: Tetanus is a vaccine-preventable disease of significant public health importance especially in developing countries. The WHO strategy for the elimination of maternal and neonatal tetanus recommends the promotion of clean delivery practices, systematic immunization of pregnant women and those in the reproductive age (15-49 years) and surveillance for neonatal tetanus. Implementation of the recommended strategy with the support of WHO, UNICEF and other partners has led to significant decline in number of cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
1
16
2
Order By: Relevance
“…For instance, women with primary and higher educational level had lower odds of receiving TT immunization when compared to those with no formal education. This finding is in contrast with previous studies that reported TT immunization was positively associated with women's level of education [14,19,29,[45][46][47]. Additionally, significantly lower TT immunization was found among women from the Temme ethnicity compared to those from another ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For instance, women with primary and higher educational level had lower odds of receiving TT immunization when compared to those with no formal education. This finding is in contrast with previous studies that reported TT immunization was positively associated with women's level of education [14,19,29,[45][46][47]. Additionally, significantly lower TT immunization was found among women from the Temme ethnicity compared to those from another ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings reveal that the proportion of pregnant women who received TT immunization was 97.8% and that of adequate doses was 82%. These findings concur with results from previous studies that reported higher prevalence of receiving TT immunization [30] but are inconsistent with studies that reported lower rates of receiving adequate doses of TT immunization [14,19,28,29]. This difference may be due to cultural practices, and financial capabilities of women needed to seek immunization services.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although there has been significant improvement in vaccination coverage in Africa, challenges remain. For example, the goal of eliminating maternal and neonatal tetanus by 2015 was missed, 2 and neonatal tetanus had only been eliminated in 34 of 47 (72%) of the WHO African Region Member States by 2015. 3 The remaining 13 countries need additional support, and those that have achieved control need to sustain this achievement through the implementation of context-specific immunization and surveillance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of the vaccine with the tetanus toxoid, tetanus is still an endemic disease in under-developed countries, and its incidence tends to increase after natural disasters. In these countries, it is a problem for public health due to the mortality associated with neonatal tetanus [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%